Structural and enzymatic features of a recombinant β-fructofuranosidase from Bifidobacterium adolescentis - Mera, Alain Eduard Monsalve (2016)
Despite the fact that Glycosyl Hydrolase Family 32 present 4 467 enzyme entries, only 14 of them have been characterized structurally. From the ten protein crystal structures deposited for Bifidobacterium adolescentis ATCC 15703 at PDB just one enzyme is related to the processing of non-digestible sugars and there is no structure of a β-fructofuranosidase. In this research we studied the biochemical properties and the structural features of a recombinant β-fructofuranosidase (BaFFse) from the healthy gut bacteria B. adolescentis ATCC 15703 (gen BAD_1325) heterologously expressed in Escherichia coli Rosetta. The enzyme was purified by nickel ion affinity chromatography and molecular exclusion chromatography; the purification process was judged by denaturing SDS-PAGE gel. Sucrose was used as a substrate for the enzyme activity assays and the amount of reducing sugars, detected by Dinitrosalycilic acid, was taken as indicator of the optimum conditions of hydrolysis for the enzyme. BaFFase crystal, grown in PEG 8K 25% (w/v) and buffer MES 0.1M pH 6.5, was diffracted at 2.44 Å and processed using the CCP4 program package. The enzyme presented a classical four-stranded five-bladed β-propeller and a C-terminal β-sandwich characteristic from the GH 32 family; however, connected to the β-propeller through a loop of 38 residues, BaFFase also presented an N-terminal β-sandwich domain, which sequence (residues 3-100 from BaFFase) did not match with any protein sequence when aligned against PDB database. Assays with Gel filtration calibration, DLS and SAXS showed that the enzyme was a stable homodimer in solution. Based on the superposition of structures using the a β-fructofuranosidase from B. longum KN29.1 we could deduced the three key aminoacids involved in the transferring of fructosyl moieties by BaFFase. A nucleophile attack is performed by the carboxylate of Asp 131, forming the fructose BaFFase intermediate; Glu 375 donates a proton, acting as an acid base catalyst and Asp 269 stabilizes the transitions state in the fructosyl transferring activity. This is the first GH32 oligomeric enzyme belonging to the bacteria kingdom. We have described a novel additional β-sandwich domain for a GH32 enzyme that increases the region of contact to form a dimer. This is the first β-fructofuranosidase crystal structure from the microorganism B. adolescentis ATCC 15703.